Testing of aluminum alloyed bolted joints for connecting aluminum rectangular hollow sections in reticulated shells. (1st September 2020) - Jiang, Yuqi; Ma, Huihuan; Richard Liew, J.Y.; Fan, Feng
Highlights: New joint for connecting aluminum rectangular hollow section members is proposed. Six different full-scale ARH joints are tested under an out-of-plane bending moment. The M-Φ curves, stress variation, and failure modes of the ARH joint are obtained. A bilinear model is proposed to summarize the M-Φ curves of the joint. The influence of different factors on mechanical behavior of ARH joints is analyzed. Abstract: A new joint system for connecting aluminum alloy rectangular hollow section (ARH) members is proposed to overcome the problem of connecting rectangular tubes using the traditional Temcor joint. The structural performance of the ARH joint system under an out-of-plane bending moment is studied experimentally. The moment-rotation ( M-Φ ) curves, stress variation, and failure modes of the ARH joint obtained from the tests are discussed. A bilinear model is proposed to summarize the M-Φ curves of the joint. The influence of the key parameters, gusset thickness and bolt quantity on the mechanical behavior of the ARH joint is analyzed. Subsequently, finite element analysis is conducted to investigate the moment rotational behavior of the ARH joint. The comparison between the experimental and numerical results proves that the proposed finite element model is accurate enough and can be used to study the moment resistance behavior of the ARH joint system. The results show that the proposed ARH joint, for connecting rectangular hollow section members, can be considered as a semi-rigid connection. This study provides a reference for the practical application of the ARH joint in reticulated structures made of aluminum rectangular members.